Home Care Providers to the Rescue: A Novel First-Responder Programme - Hansen, Steen M. (PLoS One, 2015)
AIM: To describe the implementation of a novel first-responder programme in which home care providers equipped with automated external defibrillators (AEDs) were dispatched in parallel with existing emergency medical services in the event of a suspected out-of-hospital cardiac arrest (OHCA). METHODS: We evaluated a one-year prospective study that trained home care providers in performing cardiopulmonary resuscitation (CPR) and using an AED in cases of suspected OHCA. Data were collected from cardiac arrest case files, case files from each provider dispatch and a survey among dispatched providers. The study was conducted in a rural district in Denmark. RESULTS: Home care providers were dispatched to 28 of the 60 OHCAs that occurred in the study period. In ten cases the providers arrived before the ambulance service and subsequently performed CPR. AED analysis was executed in three cases and shock was delivered in one case. For 26 of the 28 cases, the cardiac arrest occurred in a private home. Ninety-five per cent of the providers who had been dispatched to a cardiac arrest reported feeling prepared for managing the initial resuscitation, including use of AED. CONCLUSION: Home care providers are suited to act as first-responders in predominantly rural and residential districts. Future follow-up will allow further evaluation of home care provider arrivals and patient survival.